PERSEPSI DAN TINDAKAN LANSIA TENTANG RHEUMATOID ARTRITIS DI POSYANDU LANSIA KELURAHAN LOSUNG WILAYAH KERJA PUSKESMAS PADANGMATINGGI KOTA PADANGSIDIMPUAN TAHUN 2015 - Purba, Iqbal Octari; Safitri, Julidia (Jurnal Kesehatan Ilmiah Aufa Royhan, 2018)
The increasing number of elderly people in many countries, including developingcountries, will change the national and global population profile. The prevalence ofRheumatoid Arthritis in Indonesia is only 0.1-0.3% in the adult group and 1: 100thousand inhabitants in the group of children, a total estimated only 360 thousandpatients in Indonesia, although the low prevalence of this disease is very progressive andmost often causes defective. This study aims to determine how the perceptions and actionsof elderly people about Rheumatoid Arthritis in the Posyandu Elderly in Losung Village,Padangmatinggi Public Health Center, Padangsidimpuan City in 2015. This study uses aqualitative approach that is defined as a research procedure that produces descriptivedata. The informants in this study were taken using a purposive technique, namely theelderly who visited the Posyandu of the elderly. Data collection techniques used wereinterviews. The data collected was analyzed manually, namely by writing down the results of the study in the form of a transcript of the results of an in-depth interview, then summarizing it in the form of a matrix arranged according to the standard language of the informant's answers. The results of interviews with all informants obtained a statement that complaints are often felt, often aches - stiffness, stiffness, redness accompanied by swelling in the ankles and hands, all informants can answer complaints that are often felt by patients with Rheumatoid Arthritis. It is expected that the respondents can take care of their health so they are not susceptible to disease, and utilize existing health facilities